Pembentukan Karakter Disiplin dan Tanggung Jawab Siswa Dalam Kegiatan Ekstrakurikuler Palang Merah Remaja - Syarifah Aini Siregar; M. Anwar Azhari Lubis (Madani: Jurnal Ilmiah Multidisiplin, 2025)
A strong and superior character will determine how students think, behave, and act when participating in activities at school. This study aims to form the character of discipline and responsibility of students in extracurricular activities of the Youth Red Cross. This study is qualitative and descriptive. Data collection techniques using observation, interviews, and documentation. The results of the study indicate that: 1) How to instill knowledge about discipline and responsibility through the Youth Red Cross extracurricular. 2) How to instill feelings of discipline and responsibility in students through the Youth Red Cross extracurricular. 3) Habituation of discipline and responsibility in students through the Youth Red Cross is realized in routine training, both weekly and intended for all students. Based on the results of the study, it can be concluded that instilling knowledge of discipline and responsibility character with the Youth Red Cross extracurricular is an effective medium for instilling knowledge of discipline and responsibility in students. Instilling feelings of discipline and responsibility in students is The Youth Red Cross Extracurricular has proven to be an effective medium for instilling feelings of discipline and responsibility in students. The cultivation of discipline and responsibility character through the Youth Red Cross extracurricular is realized in routine training. The suggestion for schools is to involve instructors to participate in Youth Red Cross training courses